Thermal Stress Analysis for Barrel and Screw Component in The Plastic Waste Machine Using Finite Element Method - Maulana, Ari -; Yusup, Ilham Maulana; Syafrizal, Fariz -; Adha, Rizky -; Satria, Dhimas -; Hendra, Hendra - (Department of Mechanical Engineering, Universitas Andalas, 2023)
Plastic waste causes negative impacts for environmental such as air pollution, water pollution, and others. To solve this problem, a plastic processing machine was made. Barrels and screws are the most important components of this machine. Aims in this study to find maximum thermal stress for the barrel and screw component in the plastic waste machinery with temperatures operation 260 0C and variation material. Finite element method are used to simulate and show that the results for the barrel using alloy steel has a maximum von Mises stress of 618,292 MPa. Â For displacement, this alloy steel material also has a maximum displacement of 0.612 mm. For the screw material used by using AISI 4340 Steel has a maximum von Mises stress of 849.997 MPa and the maximum displacement of 0.673 mm. It can be said that this material is still safe when used for barrels and screws component in the plastic waste machine processing.